Pembiayaan PLs, Kinerja Keuangan dan Profitabilitas BPR Syariah di Indonesia: Covid-19 sebagai Moderating - Chitra Yuliashri Katili (Scimadly Publishing, 2022)
This research will analyze the effect of financial performance, PLS-based financing, financing risk, and Covid-19 on the Profitability of Islamic Rural Banks (IRB) in Indonesia. Covid-19 is also a moderating variable affecting financial performance, PLS-based financing, and financing risk. This study used the quantitative method. The analysis was performed using SEM-PLS. Consists of three variables and indicators used. The first variable is financial performance consisting of CAR, FDR, Assets, Third Party Funds (DPK), Total Financing, and the number of Sharia BPR offices. Second, PLS-based financing consists of mudharabah and musharakah financing. Third, financing risk is represented by non-performing financing (NPF). The results of this study show that the hypothesis proposed has yet to be fully proven. But what must be the concern of BPR Syariah is that PLS-based financing is indicated actually to reduce profitability if not managed properly. This study is different from previous studies that used regression-based analysis only. This research uses Structural analysis using Structural Equation Modelling (SEM) PLS. As well as using Covid-19 as a moderating variable.